2017
DOI: 10.12659/msm.899905
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelial Nitric Oxide Synthase Gene T-786C Polymorphism Increases Myocardial Infarction Risk: A Meta-Analysis

Abstract: BackgroundPolymorphisms of the endothelial nitric oxide synthase (eNOS) gene are reportedly associated with myocardial infarction (MI) risk. However, definitive evidence of this association is lacking. In this study, we investigated the potential association of eNOS gene polymorphisms with MI risk by conducting a meta-analysis of studies evaluating this association.Material/MethodsPubMed, Web of Knowledge, ScienceDirect, China National Knowledge Infrastructure (CNKI), WanFang, and Database of Chinese Scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The C allele associated with the risk of MI in our study is related to downregulation of mRNA expression and, correspondingly, the eNOS protein level [40]. Our data are consistent with the findings reported in other publications [41].…”
Section: Discussionsupporting
confidence: 93%
“…The C allele associated with the risk of MI in our study is related to downregulation of mRNA expression and, correspondingly, the eNOS protein level [40]. Our data are consistent with the findings reported in other publications [41].…”
Section: Discussionsupporting
confidence: 93%
“…Yet, SNP in promoter region of eNOs gene was strongly associated with a risk of cardiovascular and renal disease in several populations [28,29] . Moreover, meta-analysis provided by Kong XZ et al (2017) [30] is reported that 786СС polymorphism in eNOs gene corresponded well with increased risk of primary MI. Therefore, negative impact of the 786СС polymorphism in eNOs gene on a risk of death after MI was determined in manyfore populations [31][32][33][34] .…”
Section: Discussionmentioning
confidence: 95%
“…Previous preclinical and clinical studies have been shown that genetic deletion of promoter region of eNOs gene -single nucleotide polymorphisms (SNP) T786C -frequently associated with lowered NO production [4] . SNP T786C in eNOs gene corresponded to lipid infiltration of vascular wall, apoptosis of mature and progenitor endothelial cells, oxidative stress-induced microvascular inflammation, mononuclear infiltration, proliferation of vascular smooth muscle cells (VSMCs), accumulation of extracellular matrix components, and platelet aggregation on the surface of endothelium [5][6][7] . Collectively, impaired eNO bioavailability was found as main trigger for endothelial dysfunction, accelerating atherosclerosis, and thrombosis [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia and lipids in peripheral blood were not the factors contributing to the impact of 786CC eNOS polymorphism on clinical outcomes, even though T2DM was determined as a predictor. Previous clinical studies have shown that sev-eral comorbidities (T2DM, dyslipidemia, the severity of atherosclerosis, smoking) were reported as cofactors influenced on natural evolution of acute myocardial infarction 13,32 . Early investigations were not confirmed as predictive potency of 786CC in eNOs gene polymorphism in acute STEMI patients 17,18 ,as these studies were performed before the primary PCI era.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is an established factor in maintaining endothelial function and vascular wall integrity [1][2][3][4] . Genetic polymorphisms of endothelial NO synthase (eNOs) is associated with altered NO levels in peripheral blood, increased levels of plasma low-density lipoproteins (LDL) and oxidized lipids, suppressed the production of vascular endothelial growth factor and increased fasting glucose 5-7. These findings were reported to have clinical significance in acute ST-segment elevation myocardial infarction (STEMI), stable coronary artery disease (CAD), asymptomatic atherosclerosis, heart failure (HF), abdominal obesity, hypertension, diabetes mellitus, and restenosis and thrombosis after primary percutaneous coronary artery intervention (PCI) 8-10. Previous studies have shown that polymorphism in promoter region of eNOs gene (T786C) in STEMI patients is corresponding with impaired pleiotropic effect of NO, which led to adverse cardiac remodeling, early stent thrombosis and restenosis after PCI [11][12][13][14] . T786C eNOs genotype can predict cardiovascular (CV) mortality in high-risk patients 15 and individuals with stable CAD 16 , while several studies have reported controversies issues regarding the discriminative values of T786C eNOs genotype in STEMI patients 17,18 .…”
Section: Introductionmentioning
confidence: 99%